Facile preparation of poly (2, 6-dimethyl-1, 4-phenylene oxide)-based anion exchange membranes with improved alkaline stability. (3rd May 2019) - Jia, Guangyao; Zhu, Zhengfang; Li, Shining; Lu, Yu; Zhu, Yuanqin
Abstract: Traditional quaternary ammonium (QA)-type anion exchange membranes (AEMs) usually exhibit insufficient alkaline stability, which impede their practical application in fuel cells. To address this issue, a facile method for the simple and accessible preparation of QA-type AEMs with improved alkaline stability was developed in this study. A series of novel AEMs (QPPO-xx-OH) were prepared from commercially available poly (2, 6-dimethyl-1, 4-phenylene oxide) (PPO) and 3-(dimethylamino)-2, 2-dimethyl-1-propanol, via a three-step procedure that included bromination, quaternization, and ion exchange. Scanning electron microscopy revealed that dense, uniform membranes were formed. These QPPO-xx-OH membranes exhibited moderate hydroxide conductivities with ranges of 4–15 mS/cm at 30 °C and 12–36 mS/cm at 80 °C. When tested at similar ion exchange capacity (IEC) levels, the IEC retentions of QPPO-xx-OH membranes were 16–22% higher than that of traditional PPO membranes containing benzyltriethylammonium ions, after immersed in 2 M NaOH aqueous solution at 60 °C for 480 h, and the QPPO-47-OH membrane displayed excellent alkaline stability with the IEC retention of 92% after 480 h. In addition, the QPPO-xx-OH membranes also exhibited robust mechanical properties (tensile strength up to 37.6 MPa) and good thermal stability (onset decomposition temperature up to 150 °C). This study provides a new and scalable method for the facile preparation of AEMs with improved alkaline stability. Graphical abstract: Image 1 Highlights: A facile method was proposed to prepare AEMs with improved alkaline stability. QPPO-xx-OH was prepared from commercially available polymer matrix and QA precursor. QPPO-xx-OH exhibit high alkaline stability and robust mechanical properties.